Special Economic Zones Promising to Increase Investment Activity (The Peerian Journal, 2023)
The essence of the special economic zone, the theoretical basis for the development of investment activity in the region, the main characteristics of the investment activity of the special economic zone, and the prospect of increasing the investment activity of the special economic zone are presented